2015
DOI: 10.1021/acs.jpclett.5b00905
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian Guide to Symmetry Properties of the Reference Cubic Structure of 3D All-Inorganic and Hybrid Perovskites

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(115 citation statements)
references
References 31 publications
2
113
0
Order By: Relevance
“…9,10 Moreover, this family of compounds can be found in many different crystal structures. To conduct our survey we decided to start from the highly symmetrical Pm3m (n 221) reference phase, 52 observed in the high temperature phase of numerous hybrid perovskites. [54][55][56][57] From this point we follow different phase transitions ( Figure 2).…”
Section: Dresselhaus Spin Splittingsmentioning
confidence: 99%
“…9,10 Moreover, this family of compounds can be found in many different crystal structures. To conduct our survey we decided to start from the highly symmetrical Pm3m (n 221) reference phase, 52 observed in the high temperature phase of numerous hybrid perovskites. [54][55][56][57] From this point we follow different phase transitions ( Figure 2).…”
Section: Dresselhaus Spin Splittingsmentioning
confidence: 99%
“…A detailed analysis of the perovskites symmetry can be found in the literature. [33][34][35] Most of the basic properties of inorganic halide perovskites may be understood from an analysis of the cubic phase. In this phase crystals have the point group O h coinciding with the group of the wave vector at the R point of the Brillouin zone, where the band extrema are located.…”
Section: Bandstructure Of Inorganic Halide Perovskitesmentioning
confidence: 99%
“…In inorganic bulk perovskites, all phase transitions occur well above room temperature [50,51]. An elaborate review of the perovskites symmetry can be found in the literature [52,53]. However, a detailed knowledge of the point-group symmetry and an appropriate irreductible representations become crucial to describe the band-edge excitons of highly anisotropic perovskite NCs.…”
Section: Introductionmentioning
confidence: 99%